Assessing the usability of University websites from users' perspective - A. Jabar, Marzanah; Usman, Usman Abbas; Awal, Aisha (American-Eurasian Network for Scientific Information, 2013)
University websites aim at providing up-to-date information and services to students,lecturers, administrators and other users in efficient ways. Unfortunately, website design is often driven by technology, organisational structure, or business objectives, rather than by its usability from the perspective of students in university Website designers end up developing websites which do not meet the needs of the primary users (students). The study evaluated the usability of the University website from the perspective of of 364 university students and investigated whether area of specialisation has significant impacts on these usability factors. This aim is achieved by using a questionnaire based on the five factors of usability defined by WAMMI (Website Analysis and Measurement Inventory): attractiveness, controllability, helpfulness, efficiency and learnability.The results identifies the usability factors that need to be given more consideration when designing an educational website and shows that different perspectieves derived from area of specialization gives different evaluation.